Characterization of Guideline Evidence for Off-label Medication Use in the Intensive Care Unit. (July 2017) - Shoulders, Bethany R.; Smithburger, Pamela L.; Tchen, Stephanie; Buckley, Mitchell; Lat, Ishaq; Kane-Gill, Sandra L.
Background: Non–Food and Drug Administration (FDA) or off-label medication prescribing occurs commonly in the intensive care unit (ICU). Off-label medication use creates a concern for untoward adverse effects; however, this worry may be alleviated by supportive literature.Objective: To evaluate the evidence behind off-label medication use by determining the presence of guideline support and compare graded recommendations to an online tertiary resource, DRUGDEX.Methods: Off-label medication use was identified prospectively over 3 months in medical ICUs in 3 academic medical centers. Literature searches were conducted in PubMed and the national guideline clearinghouse website to determine the presence of guideline support. DRUGDEX was also searched for strength-of-evidence ratings to serve as a comparator.Results: A total of 287 off-label medication indication searches resulted in 44% (126/287) without identified evidence; 253 guidelines were identified for 56% (161/287) of indications. Of the published guidelines, 89% (226/253) supported the off-label indication. In the DRUGDEX comparison, 67% (97/144) of guideline gradings disagree with DRUGDEX, whereas 33% (47/144) of the gradings matched the online database.Conclusion: Because more than half of off-label medication use has the benefit of supportive guidelines recommendations and a majority of gradings are inconsistent with DRUGDEX, clinicians should consider utilizing guidelines to inform off-label medication use in the ICU. Still, there is a considerable amount of off-label medication use in the ICU that lacks supporting evidence, and use remains concerning because it may lead to inappropriate treatment and adverse events.